Analisis SWOT Pemanfaatan Media Digital untuk Peningkatan Literasi Keuangan Syariah di Yayasan Phatnawitya School Yala - Siregar, Elpi Rahmi; Rahmayati, Rahmayati (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
The low level of Islamic financial literacy among students has become a significant challenge for Islamic educational institutions in instilling an understanding of economic principles based on sharia values from an early age. Therefore, educational institutions are required to adopt innovative learning approaches, including the use of digital media as an effective educational tool. This study aims to examine the use of digital media in improving Islamic financial literacy through a SWOT analysis at Phatnawitya School Yala. This research employed a descriptive qualitative method, with data collected through in-depth interviews, observation, and documentation. The interviews involved several key informants, including foundation administrators, teachers, parents, and other related stakeholders. The findings indicate that the implementation of digital media in Islamic financial literacy education at Phatnawitya School Yala is carried out through a combined approach that integrates conventional classroom learning with digital platforms such as educational videos, social media, and interactive online materials. This approach has been shown to increase students’ learning interest, facilitate their understanding of Islamic financial concepts, and expand access to financial education for both students and parents. However, the study also identifies several challenges, including the need for stronger moral filtering in digital media usage and the development of educational content in local languages to enhance students’ comprehension. Therefore, optimizing digital learning strategies integrated with Islamic values is essential for improving the effectiveness of Islamic financial literacy education in schools.